Solvay history of a multinational family firm - Bertrams, Kenneth. (Cambridge University Press, 2013)
"Ernest Solvay, philanthropist and organizer of the world-famous Solvay conferences on physics, discovered a profitable way of making soda ash in 1861. Together with a handful of associates, he laid the foundations of the Solvay company, which successfully branched out into other chemicals, plastics and pharmaceuticals. Since its emergence in 1863, Solvay has maintained world leadership in the production of soda ash. This is the first scholarly book on the history of the Solvay company, which was one of the earliest chemical multinationals and today is among the world's twenty largest chemical companies. It is also one of the largest companies in the field to preserve its family character. The authors analyze the company's 150-year history (1863-2013) from economic, political and social perspectives, showing the enormous impact geopolitical events had on the company and the recent consequences of global competition"--